Pengaruh Corporate Governance dan Corporate Social Responsibility terhadap Kualitas Laba dan Nilai Perusahaan - Hennyta Hutapea (Journal of Applied Accounting and Taxation, 2019)
This study aims to examine the effect of corporate governance (CG) and corporate social responsibility (CSR) disclosure of earnings quality and firm value. Corporate governance with board diversity is measured from the aspect of age and background study of board members. CSR disclosure in the company’s annual report is measured by the score of Global Reporting Initiative (GRI). This study measures the company’s earnings quality with discretionary accruals (DA), and the firm value with tobin’s q ratio. This study use a sample of 160 non-financial companies listed on the Indonesia Stock Exchange (BEI), so the total observations in this study are 640 samples. The result of this study provide empirical evidence that age and background study of board members don’t affect the quality of earnings and firm value, but the CSR activities affect the firm value.